Sexual and reproductive health services utilization and associated factors among adolescents attending secondary schools - Chaltu Abdurahman; Lemessa Oljira; Saba Hailu; Melkamu Merid Mengesha (BMC, 2022)
Plain language summary Background Sexual and reproductive health (SRH) refers to physical and emotional wellbeing and includes the ability to be free from unwanted pregnancy, unsafe abortion, sexually transmitted infections including HIV/AIDS, and all forms of sexual violence and coercion. Components of the SRH services are important to reduce adolescent reproductive health risks and problems. This paper reports on the frequency of in-school adolescents who utilized SRH services and the factors that determined it. Methods we collected data from 642 in-school secondary school adolescents, aged 15-19 years, in Haramaya district, East Ethiopia. The data were collected from two schools, one from rural and the other from urban areas, using lottery method from the available schools in the district. A face-to-face interview was conducted to obtain data from the adolescents in the selected secondary schools. Result Out of 642 in-school adolescents, 23.5% utilized SRH services in Haramaya District. Adolescents who previously received SRH information, who knew SRH services providing facility, aware of SRH service components, and those who live not close to the SRH facilities were utilized the SRH services more often compared to their friends. Conclusion Nearly one-in-four secondary school adolescents (23.5%) utilized SRH services. Targeted promotion of SRH providing facilities and SRH service components aimed at awareness creation could improve adolescents' utilization of SRH services.